Pengaruh sadar wisata, kemenarikan fasilitas dan jarak terhadap minat berkunjung kembali pada objek wisata Merangin Garden di Kabupaten Merangin - Muttakin Ab; Zulfanetti Zulfanetti; Jaya Kusuma Edy (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2020)
Tourism is the fastest growing foreign exchange earning subsector and the increase is almost happening in all regions, Merangin regency has a great potential in tourism. The purpose of this study is to analyze the characteristics of visitors or tourists, identify factors that affect the interest of tourists to visit again, and how important is the participation of the community around the tourism object. The data used in this study are primary data obtained from questionnaires and direct interviews with a sample of 35 people. The sampling method used is convenient random sampling. The data analysis tool used is quantitative with multiple liner analysis used Eviews 9 software. Merangin garden tourist characteristics in Merangin district are known that the average age of the visitors is 39. The sex of visitors or tourists is male, education is high school / equivalent, the number of dependents of visitors is 4 people where visitors live are Merangin and surrounding communities. The distance between visitors to the Merangin Garden attraction is 30 km on average.